Trends in production and ecological consumption [Tendencias de producción y consumo ecológico] (2018)
The consumption of ecological products and services is an emerging practice that is influencing the inhabitants of the region of Antioquia. Determining the main trends in this type of consumption will enable the business sector to adapt its value propositions, products and services to a new consumer. The results establish a classification of consumers with a tendency towards green consumption and expose some aspects of common situations in companies with clean and sustainable production practices. © 2018.